A VERY RARELY SEEN CONGENITAL ANOMALY: PRESTERNAL BRONCHOGENIC CYST - Özel, Ş. Kerem; Tuğtepe, Halil (Fırat University, 2001)
Bronchogenic cysts are formed during the budding of the tracheal diverticula and ventral foregut in the embryological period. These cysts are seen generally in the thoracic cavity and very rarely in the presternal region. In this report we want to present a case of presternal bronchogenic cyst whose diagnosis was made during pathological examination after the surgery. During microscopical examination histological elements of the tracheobronchial tree can be seen. On the other hand in case of chronic infection this histological significance can be obscure. The clinical diagnosis can be difficult and the exact diagnosis can only be made with pathological examination. In the differential diagnosis, teratomas, branchial cleft anomalies and dermoid cysts are important. The definitive treatment can only be surgical excision due to bleeding and infection. There is recent information about malign degeneration of the bronchogenic cysts located in the thoracic cavity. Bronchogenic cysts should be considered during surgical consultation of presternal masses. The awareness of this entity will avoid inefficient therapeutical approach to the patient.

Bronkojenik kistler embriyolojik hayatta trakeal divertikülün veya ön foregut'un bölünmesi sırasında oluşmaktadır. Genelde toraks içinde görülmekle beraber çok nadir olarak presternal bölgede de bulunabilir. Burada, operasyon sonrasında patolojik inceleme ile tanısı konulmuş bir presternal bronkojenik kist olgumuzu sunmak istiyoruz. Bu lezyonun özelliği trakeobronşiyal ağaca ait yapıların mikroskopik incelemede görülmesidir. Ancak kronik enfeksiyon durumunda bu yapıların hepsinin görülmesi mümkün olmayabilir. Klinik olarak aynı bölgede yer alan kitlelerle ayırıcı tanısı güç olmakla beraber esas tanısı ancak histoloji ile konulabilmektedir. Ayırıcı tamda özellikle teratomu, brankial kleft anomalilerini ve dermoid kistleri vurgulamak gerekmektedir. Kanama ve enfeksiyon nedeniyle kesin tedavisi cerrahidir. Ayrıca bazı yayınlarda, intratorasik yerleşimli bronkojenik kişilerdeki malign dejenerasyona ait bilgiler mevcuttur. Bronkojenik kistler, özellikle presternal bölgede yerleşmiş olan kitlelerde ayırıcı tanıda akla gelmesi gereken patolojilerden bir tanesidir. Bu antitenin iyi bilinmesi, eksik tedavi yaklaşımlarının önüne geçilmesi bakımından önem taşımaktadır.
NADİR GÖRÜLEN BİR KONJENİTAL ANOMALİ: PRESTERNAL BRONKOJENİK KİST